ANALISIS PELAKSANAAN PROGRAM DAN KEBIJAKAN KESELAMATAN DAN KESEHATAN KERJA PADA DEPARTEMENT PGA DI RUMAH POTONG AYAM (RPA) PT CIOMAS ADISATWA SIDOARJO - Al-Fajri, Muhammad Amin; Almanshur, Fauzan (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2022)
The purpose of this research is to to analyze the Occupational Health and Safety Program and Policy at the PGA Department at the Chicken Slaughterhouse (RPA) PT Ciomas Adisatwa Sidoarjo.In this study used descriptive qualitative research with data collection techniques Observation, Interview, and Documentation. The sample of this research is Chicken Slaughterhouse Employees at PT Ciomas Adisatwa Sidoarjo who were selected using purposive sampling. Data collection techniques used in this study are interviews, observation, documentation.The results of this research are the Occupational Health and Safety Program and Policy at the PGA Department at the PT Ciomas Adisatwa Sidoarjo Chicken Slaughterhouse (RPA), namely: 1) Establishing an Emergency Response Team and Food Safety; 2) Preparation of Emergency Preparedness and Response Implementation Procedures; 3) Providing K3 and Social Security Facilities. The application of medical devices provided to PT Ciomas Adisatwa Sidoarjo was carried out properly